The future of agriculture in South Asia -- W(h)ither the Small Farm? Summary Paper from the International Conference on Sustainable Food Security For All By 2020 - Gulati, Ashok (International Food Policy Research Institute, 2001)
Gulati speaks of South Asian agriculture and the emerging challenges it faces. He addresses population growth and the growing scarcity of land and water. He raise concerns about the globalization of agriculture and the need for more investment in R&D and rural infrastructure.